Midlife measures of lipid fractions and fasting glucose are associated with late‐onset Alzheimer disease. (31st December 2021) - Zhang, Xiaoling; Tong, Tong; Chang, Andrew; Ang, Ting Fang Alvin; Tao, Qiushan; Auerbach, Sandford H.; Devine, Sherral; Qiu, Wendy; Mez, Jesse; Massaro, Joseph; Lunetta, Kathryn L.; Au, Rhoda; et al.
Abstract: Background: Measures of cardiovascular and metabolic disease are well‐established risk factors for late‐onset Alzheimer disease (AD). However, it is poorly understood whether exposure to these risk factors in early adulthood is associated with AD in late‐life. Method: Association of incident AD occurring after age 60 with measures of lipid fractions, hypertension, diabetes, blood glucose, BMI and smoking obtained prospectively across nine quadrennial examinations was evaluated in the Framingham Heart Study (FHS) Offspring cohort (n=5, 124) using Cox proportional hazard models. Age‐ and sex‐adjusted models were tested for each risk factor measured at each exam and within three age groups (early adulthood=35‐50, middle adulthood=51‐60, late adulthood=61‐70). Additional models included covariates for risk factor‐specific treatment and APOE ε4 carrier status. Result: During a mean follow‐up period of 31.7±6.7 years, a diagnosis of incident AD was established for 271 participants. A 15 mg/dL increase in high‐density lipoprotein cholesterol (HDL‐C) measured during early adulthood and middle adulthood was associated with a 19.1% decreased risk of AD in each group (HR=0.81 [95%CI 0.70, 0.96], P=0.011 and HR=0.81 [0.67, 0.97], P=0.019, respectively). An increased risk of AD was also associated with 15 mg/dL increases of triglyceride (TG) (HR=1.05 [1.002, 1.10], P=0.023) and low‐density lipoprotein cholesterol (LDL‐C) (HR=1.06 [1.003, 1.12], P=0.041) measured in early adulthood. A 15 mg/dL increase in fasting blood glucose (FBG) measured during middle adulthood was associated with a 11.0% increased risk of AD (HR=1.11 [1.03, 1.20], P=0.0039). These findings remained significant after adjusting for treatment. Survival analysis showed that AD risk was significantly higher and occurred earlier among individuals with FBG in the pre‐diabetic (100‐126 mg/dL) and diabetic (>126 mg/dL) ranges compared to those with normal FBG (<100 mg/dL) in middle adulthood (P=0.038), but not in late adulthood. Conclusion: HDL‐C, LDL‐C, TG and FBG levels measured in cognitively normal individuals between ages 35 and 60 years are significantly associated with incident AD several decades later. Our findings suggest that careful management of cholesterol and glucose levels beginning in early adulthood can lower AD risk in later life including among APOE ε4 carriers, in addition to the benefits of promoting cardiovascular and metabolic health.